Local and nanoscopic structure of potassium triflate-doped siloxane-polyoxyethylene ormolytes - Chaker, J. A.; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Goncalves, M. C.; Correia, S. M. Gomes; Bermudez, V. de Zea; Judeinstein, P.; Briois, V.; Craievich, A. F. (Elsevier B.V., 2006)
Siloxane-poly(oxyethylene) hybrids obtained by the sol-gel process and containing short polymer chain have been doped with potassium triflate (KCF3SO3). The local structure of these hybrids was investigated by X-ray absorption spectroscopy near the potassium K-edge. Small angle X-ray scattering was used to determine the structure at the nanometer scale. Results revealed that at low and medium potassium concentration (n = [O][K] >= 8, where n represents the molar ratio of ether-type oxygen atoms per alkaline cation) the cations interact mainly with the polymer chains, while at larger doping level (n < 8) the formation of a polyehter:KCF3SO3 Complex is observed. The nanoscopic structure of the hybrids is also affected by doping. By increasing the doping level, decreasing trends in the electronic density contrast between siloxane nanoparticles and polyether matrix and in the siloxane interparticle distance are observed. At high doping level the small angle X-ray scattering patterns are strongly modified, showing the disappearance of the correlation peak and the formation of a potassium-containing nanophase. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: nanocomposites; sol-gel; organic-inorganic hybrids